SAP ERP Analysis as the Key of the Company's Procurement Process in the Use of Social Media - Serumena, Dedy Ricardo; Santoso, Alb Joko; Kristyanto, B. (International Journal of Supply Chain Management, 2019)
AbstractResearchers analysis is focused on a logistic company in Maluku, with fish processing as its raw material. They understand about the supply chain strategy, but in fact, the amount and value of production from year to year is not very stable, lack of fun operational in the process and in building relations with the positive impression of the community. The determining method for researchers analysis is based on the quantitative approach. The results of this approach provide almost 90% of the information that is needed. The researchers think that technically, SAP ERP Enterprise Core is able to compensate for the implementation of their ERP and SAP Business Suite integrated solution packages, such as SAP CRM (Customer Relationship Management), SAP SCM (Supply Chain Management), SAP SRM (Supplier Relationship Management) and SAP PLM (Product Life Cycle Management). SCM, PLM in their supply chain strategy and CRM, SRM are as a customer service technique in a fun sales process with an integrated information system network through rapidly growing social media developments. The results of these managements are very influential on their business process. The effect is not only for the company but it also has a great influence on the welfare of local communities (fishermen) in producing good quality of raw materials. According to researchers, the water has an area of 658,294.69 km or reaching 92.4%, as much as 20% of the potential of capture fishery is in this region, hence the increase of food source and fish nutrition, community welfare (fishermen), company development In Maluku should remain in monitor and increase from year to year.